Peningkatan Penggunaan Social Learning Network Bagi Siswa-Siswi MTSN 2 Bengkulu Tengah - Rachayu, Imma; JumiatiSiska; Diah; Fitria , Yenni; Luthfia , Izza (Universitas Dehasen Bengkulu, 2022)
This study aims to explore and analyze the improvement of Social Learning Network (SLN) usage among students of MTsN 2 Bengkulu Tengah. SLN is a digital platform that enables students to share knowledge, communicate, and collaborate within a socially connected learning environment. The research was conducted using a quantitative approach, employing survey methods and statistical data analysis. The research sample consisted of 100 students from MTsN 2 Bengkulu Tengah. The research instrument used was a questionnaire developed by the researcher. The collected data were analyzed using descriptive and inferential analysis techniques. The results of this study indicate a significant increase in the usage of SLN among students of MTsN 2 Bengkulu Tengah after its implementation. It was found that the use of SLN improved students' access to learning resources, facilitated communication and collaboration among students, and enhanced their learning motivation. Additionally, the study identified several factors influencing the usage of SLN, such as students' technological abilities, teacher support, and their perception of the benefits of using SLN. In conclusion, the use of Social Learning Network has the potential to enhance the learning experience of students at MTsN 2 Bengkulu Tengah. With easy access, improved communication, and open collaboration, SLN can help students acquire better knowledge, increase their engagement in the learning process, and expand their social networks in the educational realm.